2009
DOI: 10.1590/s1413-78522009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da velocidade e atenuação ultra-sônica na avaliação da consolidação óssea

Abstract: Objectives: The objective of this study was to compare the in vitro ultrasonic velocity and attenuation in bone healing evaluation. Methods: Seventeen sheep weighting 37 kg in average were used, being divided into two groups of five animals each and one group of seven animals, according to the postoperative follow-up time (30, 60 and 90 days, respectively). Osteotomies were performed on the right tibiae and the intact left tibiae of the 17 animals were used as control. The healing process was monitored with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The bulk density data (table 2) agree with studies of fractures in which there is an increase in bone density together with the values of c L as the healing progresses, as opposed to the rise that occurs with attenuation, which tends to be reduced with the advancement of bone healing owing to the loss of continuity that occurs when there is a fracture (Saulgozis et al 1996, Barbieri et al 2009.…”
Section: Relationship Between Bulk Density and Acoustic Parameterssupporting
confidence: 76%
See 3 more Smart Citations
“…The bulk density data (table 2) agree with studies of fractures in which there is an increase in bone density together with the values of c L as the healing progresses, as opposed to the rise that occurs with attenuation, which tends to be reduced with the advancement of bone healing owing to the loss of continuity that occurs when there is a fracture (Saulgozis et al 1996, Barbieri et al 2009.…”
Section: Relationship Between Bulk Density and Acoustic Parameterssupporting
confidence: 76%
“…Comparison between the ultrasonic longitudinal velocity of the present study and those found in the works ofProtopappas et al 2006, Barbieri et al 2009, and Vavva et al 2008 …”
supporting
confidence: 64%
See 2 more Smart Citations